Tandem intermolecular Suzuki coupling/intramolecular vinyl triflate-arene coupling - Willis, M; Claverie, C; Mahon, M (2002)
Treatment of a benzyl substituted meso-ditriflate with boronic acids in the presence of palladium acetate, triphenylphosphine and caesium fluoride results in intermolecular Suzuki coupling followed by vinyl triflate-arene cyclisation to provide, in high yields, single regioisomers of tricyclic-carbocycles.